Structure and dynamics of the von Willebrand factor C6 domain - Chen, Po-chia; Kutzki, Fabian; Mojzisch, Angelika; Simon, Bernd; Xu, Emma-Ruoqi; Aponte-Santamaria, Camilo; Horny, Kai; Jeffries, Cy; Schneppenheim, Reinhard; Wilmanns, Matthias; Brehm, Maria A.; Gräter, Frauke; et al. (Journal of structural biology, 2022)
Von Willebrand disease (VWD) is a bleeding disorder with different levels of severity. VWD-associated mutations are located in the von Willebrand factor (VWF) gene, coding for the large multidomain plasma protein VWF with essential roles in hemostasis and thrombosis. On the one hand, a variety of mutations in the C-domains of VWF are associated with increased bleeding upon vascular injury. On the other hand, VWF gain-of-function (GOF) mutations in the C4 domain have recently been identified, which induce an increased risk of myocardial infarction. Mechanistic insights into how these mutations affect the molecular behavior of VWF are scarce and holistic approaches are challenging due to the multidomain and multimeric character of this large protein. Here, we determine the structure and dynamics of the C6 domain and the single nucleotide polymorphism (SNP) variant G2705R in C6 by combining nuclear magnetic resonance spectroscopy, molecular dynamics simulations and aggregometry. Our findings indicate that this mutation mostly destabilizes VWF by leading to a more pronounced hinging between both subdomains of C6. Hemostatic parameters of variant G2705R are close to normal under static conditions, but the missense mutation results in a gain-of-function under flow conditions, due to decreased VWF stem stability. Together with the fact that two C4 variants also exhibit GOF characteristics, our data underline the importance of the VWF stem region in VWF’s hemostatic activity and the risk of mutation-associated prothrombotic properties in VWF C-domain variants due to altered stem dynamics.
Gesehen am 08.11.2023